2021
DOI: 10.17576/jsm-2021-5008-22
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isocyanate Polyurethane (NIPU) based on Rubber Seed Oil Synthesized via Low-Pressured Carbonization Reaction

Abstract: Epoxidised rubber seed oil (ERSO) was successfully synthesized into non-isocyanate polyurethane via carboxylation method whereas peroxoformic acid was formed by in-situ reaction for epoxidation. The effects of temperature and ratio of hydrogen peroxide and formic acid to rubber seed oil carboxylation were studied. The optimum temperature for the epoxidation reaction was found at 50 °C to avoid ring opening reaction of epoxy whilst the optimum ratio of hydrogen peroxide and formic acid is equal molar of double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…As shown in Scheme 1a,b, the cyclic carbonates produced from oleic acid‐based acyl chains, the product would be a di‐urethane compound, while for the cyclic carbonated produced from linoleic acid‐based acyl chains, the product would be in polymerized form. In all the reported works of NIPU reaction, linseed oil, 70 soybean oil, 37 sunflower oil, 71 rubber seed oil, 72 and jojoba oil 73 have been used in the production. The NIPUs produced were primarily aimed at applications in elastomeric materials, 37 coatings, 71 and composites 73 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme 1a,b, the cyclic carbonates produced from oleic acid‐based acyl chains, the product would be a di‐urethane compound, while for the cyclic carbonated produced from linoleic acid‐based acyl chains, the product would be in polymerized form. In all the reported works of NIPU reaction, linseed oil, 70 soybean oil, 37 sunflower oil, 71 rubber seed oil, 72 and jojoba oil 73 have been used in the production. The NIPUs produced were primarily aimed at applications in elastomeric materials, 37 coatings, 71 and composites 73 .…”
Section: Resultsmentioning
confidence: 99%
“…Appearance of peaks at 1703, 1697, 1533, and 1247 cm À1 , were attributed to the urethane groups, N H deformation of the urethane group, and C N bending of the urethane group, respectively, 28,36 which indicated the successful formation of urethane linkages. In addition, peak formation was also observed at 3336 cm À1 which corresponded to O H or N H stretching, 72 indicating the formation of the O H group within the backbone of the PU after ring opened by BDA. When the amount of BDA was in excess (molar ratio of NIPU: BDA = 1:1.6), a peak was observed at 1654 cm À1 corresponding to C O carbonyl amide peak, resulting from the undesired aminolysis side reactions of the ester groups (Figure 1b).…”
Section: Ft-ir Analysismentioning
confidence: 97%
“…The synthesis of NIPUs at room temperature has been reported in the literature and revealed that the reaction is extremely sluggish while raising the temperature significantly increases the reactivity. [ 72 ] Both the number of hydrogen bonds and viscosity increase during polymerization. Because of this, a rise in temperature will resolve the problem and increase reaction rates.…”
Section: Parameters Affecting Polyaddition or Ammonolysis Reactionmentioning
confidence: 99%